2012
DOI: 10.1093/annonc/mdr116
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy followed by concomitant radiotherapy and weekly cisplatin versus the same concomitant chemoradiotherapy in patients with nasopharyngeal carcinoma: a randomized phase II study conducted by the Hellenic Cooperative Oncology Group (HeCOG) with biomarker evaluation

Abstract: IC with three cycles of CEP when followed by CCRT did not significantly improve response rates and/or survival compared with that of CCRT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
233
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(244 citation statements)
references
References 16 publications
8
233
2
1
Order By: Relevance
“…Another two trials (Chan et al, 2005;Hui et al, 2009) were the same in design and data with almost the same authors but different numbers of patients, and in order to avoid data reduplication, then Chan et al's trial (Chan et al, 2005) was discarded. Two trials (Fountzilas et al, 2009;Fountzilas et al, 2012) were from the same study but were reported in different follow-ups. They were both included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another two trials (Chan et al, 2005;Hui et al, 2009) were the same in design and data with almost the same authors but different numbers of patients, and in order to avoid data reduplication, then Chan et al's trial (Chan et al, 2005) was discarded. Two trials (Fountzilas et al, 2009;Fountzilas et al, 2012) were from the same study but were reported in different follow-ups. They were both included.…”
Section: Resultsmentioning
confidence: 99%
“…All satisfied the criteria of complete outcome data (He et al, 2009;Hui et al, 2009;Ma et al, 2009;Sun et al, 2009;He et al, 2011;Ruste et al, 2011;Xu et al, 2011;Chen et al, 2012;Cui et al, 2012;Fountzilas et al, 2012;Huang et al, 2012), two studies didn't satisfied the item of selective reports He et al, 2011). There were no studies reporting allocation concealment, binding of participants and personnel, and binding of outcome assessment.…”
Section: Risk Of Bias Of Eligible Studies (Figure 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we show that induction chemotherapy is not an independent predictor of OS. A phase II trial of induction cisplatin, epirubicin, and paclitaxel followed by concurrent CRT vs concurrent CRT alone did not significantly improved OS or progression free survival 18. Similarly, a randomized phase II/III trial evaluating induction gemcitabine, carboplatin, and paclitaxel followed by concurrent CRT vs concurrent CRT alone showed no significant improvement in OS or distant failure‐free survival with the addition on induction regimen 19.…”
Section: Discussionmentioning
confidence: 96%